THE IMPACT OF CLIMATE CHANGE ON SDGS 13 IN THE MALDIVES WITHIN A HUMAN SECURITY FRAMEWORK - Siti Darojatun Rizki Putri; Putri Kamilah; Calya Maharani Putri Yuzerman; Dwi Ardiyanti (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
The small islands are important for ocean resilience against climate change risk. While at the same time the small islands are facing serious problems for environmental degradation as seen through higher temperature, miscellaneous disaster, sea level rise, and so forth. Thus, the problems are getting worse for unachieved Sustainable Goals, for instance limited access to education, lower economic growth, and unaccessed economic development in the small islands. The higher risk for carbon emission in the industrialization era also involved the small islands, especially in the Pacific Ocean, where all the international trade carried out all the way through. Small Island Developing States (SIDS) for renewable energy is a matter for small islands. The lighthouses projects provide a best practice of a global partnership. Thus, a waste management system to create green energy in small islands is important. Methodology of the research is qualitative based on articles review and analyzing data from several resources such as books and legal reports of the United Nations. Hypothesis of the research is that international engagement troughs for small islands help local communities to survive and achieve SDGs in the industrialization era.